Schools for democrats : being Volume One of Industrial democracy in Great Britain : a book of readings and witnesses for workers' control. - Coates, Ken; Topham, Anthony (Spokesman Books, 1975)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: democratie; werknemers